LEGISLATING HIERARCHICAL YET HARMONIOUS GENDER RELATIONS IN THE GREAT MING CODE. Issue 1 (May 2014) - Y, J
Abstract : Drawing primarily on the Great Ming Code, this essay examines how the early Ming ruling elite defined women's legal status by way of examining gender relations. Specifically, its purpose is twofold: to explore gender relations defined in law codes and to redress the negative images that are imposed on legal regulations on women in existing literature. It argues that imperial law aimed to legislate hierarchical yet harmonious gender relations. To achieve harmony, the Great Ming Code endeavors to restrict male power and protect female rights while maintaining a hierarchical legal structure.